2020
DOI: 10.1101/2020.05.18.101600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infrared fiber optic spectroscopy detects bovine articular cartilage degeneration

Abstract: Articular cartilage (AC) is a soft connective tissue that covers the ends of articulating bones. Joint injuries may lead to degeneration of cartilage tissue and initiate development of post-traumatic osteoarthritis (OA). Arthroscopic surgeries can be used to treat joint injuries, but arthroscopic evaluation of cartilage quality is subjective. Therefore, new methods are needed for objective assessment of cartilage degeneration. Fourier transform infrared (FTIR) spectroscopy can be used to assess tissue composit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Santos et al have shown that silica core-silica clad fibers, with acrylate coating and a black nylon jacket, provided low background signal and good signal quality in in vitro measurements of brain tissue of a 6-month old pig [ 100 ]. The versatility of fiber optic probes in cartilage assessment has been shown for in vitro studies of engineered cartilage development [ 54 , 55 , 83 , 91 , 101 ], ex vivo studies of cartilage degradation [ 81 , 102 ], and in vivo arthroscopic evaluation of articular cartilage and subchondral bone [ 51 ]. Similarly, Raman spectroscopic probes have also been used to assess articular cartilage quality [ 103 ], and have been used to monitor the development of tissue engineered cartilage in vitro [ 91 ].…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al have shown that silica core-silica clad fibers, with acrylate coating and a black nylon jacket, provided low background signal and good signal quality in in vitro measurements of brain tissue of a 6-month old pig [ 100 ]. The versatility of fiber optic probes in cartilage assessment has been shown for in vitro studies of engineered cartilage development [ 54 , 55 , 83 , 91 , 101 ], ex vivo studies of cartilage degradation [ 81 , 102 ], and in vivo arthroscopic evaluation of articular cartilage and subchondral bone [ 51 ]. Similarly, Raman spectroscopic probes have also been used to assess articular cartilage quality [ 103 ], and have been used to monitor the development of tissue engineered cartilage in vitro [ 91 ].…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…Additionally, polarized infrared light can be used with FTIR imaging to reveal the zonal distribution of differently oriented collagen fibers based on the ratio of the amide I to amide II absorbances [ 69 ]. The information in these foundational studies of native cartilage has subsequently been applied in many areas of cartilage research, including towards understanding of degraded osteoarthritic tissues [ 102 , 114 , 115 , 116 ], and characterization of developing engineered constructs [ 60 , 117 , 118 , 119 ].…”
Section: Application Of Vibrational Spectroscopy For Connective Timentioning
confidence: 99%